Effect of arbuscular mycorrhizal fungi inoculation on revegetation at Nukui Dam site, Japan - Minh Thi Nguyen; Kazuhira Yokoyama; Takuya Marumoto (Vietnam Journal of Science, Technology and Engineering, 2023)
The establishment of the surviving arbuscular mycorrhizal (AM) fungi, Gigaspora margarita Becker & Hall, inoculated in revegetation at the Nukui Dam was studied. The population of AM fungi and AM colonization of three plant species Japanese hill cherry (Prunus jamasakura Sieb. ex Koidz, yamazakura-inoculated plant), eulalia (Miscanthus sinensis Anderss, susuki), and mugwort (Artemisia vulgaris Pampan, yomogi) were investigated to compare inoculated and non-inoculated treatments. The AM colonisation was enhanced in inoculated plots although natural or accidental AM fungi were involved in non-inoculated plots and successfully colonised. Coverage of soil surface was more than 80% and even reached nearly 100% in summer regardless of the soil amendment type. The number of spores and the percentage of colonisation of investigated plant roots, as well as the density of typical AM structures such as arbuscules, auxiliary cells, vesicles, and coiling hyphae by AM fungi in inoculated plots were higher than those in non-inoculated ones. Some spores were Gigaspora and Glomus-inoculated species and were relatively rich in inoculated plots of Yamazakura. There was a significant increase in the number of AM spores in inoculated treatments at a 5% confidence level (ANOVA, p<0.05) in Susuki and Yamazakura. Much more spores of isp. occurred in the rhizosphere soil of Yamazakura and Susuki plants in inoculated plots than in non-inoculated plots (2.33 and 3.73 times, respectively). The colonisation intensity and spore number in the rhizosphere were positively correlated. Therefore, inoculation at an early establishment should be important for the successive development of AM-plant symbiosis formation.